Redox controls on H and N speciation and intermolecular isotopic fractionations in aqueous fluids at high pressure and high temperature: Insights from in-situ experiments - Dalou, Celia; Le Losq, Charles; Füri, Evelyn; Caumon, Marie-Camille (Frontiers in Earth Science, 2022)
Aqueous magmatic fluids are essential to the transport of hydrogen (H), carbon (C), and nitrogen (N) from the mantle to the surface, during which changes in pressure, temperature, and redox conditions affect the chemical speciation and intermolecular isotopic fractionations of H, C, and N. Here, we performed a series of hydrothermal diamond-anvil cell experiments to evaluate the role of pressure, temperature, and redox conditions on the speciation and intermolecular fractionations of H and N during the decompression and cooling of aqueous fluids from 780 MPa and 800 °C to 150 MPa and 200 °C. We used Raman spectroscopy to investigate the distribution and exchange reactions of H and N isotopologues between water, methane, ammonia, and di-nitrogen molecules under changing physicochemical conditions. Our experiments show that upon decompression, a C- and N-bearing fluid will preferentially degas D-rich methane and 15N-rich N2, depleting the residual aqueous fluid in those isotopes. If this fluid precipitates N-rich (i.e., NH4+-bearing) minerals, the observed N isotopic fractionation is opposite to that during N2 degassing, enriching the aqueous fluid in 15N. Because these fractionations result from changes in H, C, and N speciation in the aqueous fluid, their magnitudes depend on redox conditions as well as pressure and temperature. Our new in-situ experimental results are consistent with the large H and N isotopic fractionations observed between water, methane, and ammonia species in aqueous fluids at high pressures and temperatures, although the magnitude of the fractionations in our experiments cannot be quantified. Nonetheless, our results suggest that statistical thermodynamic models likely underestimate isotopic fractionation effects for isotopic molecules under these conditions, and should account for solubility and isotopic effects of the solvent associated with the solvation of water, methane, and ammonia isotopologues in aqueous fluids. This work has significant implications for interpreting isotopic measurements of natural samples from hydrothermal systems because it offers insights into isotopic fractionations in multicomponent and multiphase systems under hydrothermal temperatures and pressures.